Injection of ramipril into the lateral ventricle interferes with the drinking response induced by pharmacological and natural thirst stimuli - Saad, W. A. [UNESP]; Luiz, A. C. [UNESP]; Camargo, L. A.A. [UNESP]; Menani, J. V. [UNESP]; Renzi, A. [UNESP]; Silveira, J. E.N. [UNESP]; Paulino, M. A. [UNESP] (My University, 1994)
We investigated the effects of ramipril, an angiotensin I-converting enzyme (ACE) inhibitor, on water intake by male Holtzman rats (250-300 g) with cannulae implanted into the lateral ventricle. Intracerebroventricular (icv) injection of ramipril (1 μg/μl) significantly reduced drinking in response to subcutaneous (sc) injection of isoprenaline (100 μg/kg) from 8.49 ± 0.69 to 2.96 ± 0.36 ml/2 h, polyethyleneglycol (PEG) (30% w/v, 10 ml/kg) from 9.51 ± 2.20 to 1.6 ± 0.34 ml/2 h or water deprivation for 24 h from 12.61 ± 0.83 to 5.10 ± 1.37 ml/2 h. Ramipril had no effect on water intake induced by cellular dehydration produced by sc injection of hypertonic saline (2 M NaCl). These results are consistent with the hypothesis that ramipril acts as an ACE-blocking agent in the brain. The possibility that ramipril is transformed to ramiprilat, the active drug, by the brain is suggested.
Keywords: angiotensin; central nervous system; ramipril; water intake